Stanley Péan's Intertextual Détours: The Forest for the Trees. (June 2020) - Duff, Christine
Abstract : The intense intertextuality of Stanley Péan's novels belies their most common categorization as thriller or fantastical horror genre fiction. This little-studied Québec writer's work is replete with explicit and oblique references to texts from a wide variety of times, places, and cultural contexts. Examining selected intertexts in Péan's three novels for adults – Le tumulte de mon sang (1991), Zombi blues (1996) and Bizango (2011) – this article argues that the tactical adoption of mystery and thriller conventions camouflages the works' deeper social commentary. Using Édouard Glissant's theory of Détour as a critical framework for textual camouflage, this article shows how Péan's texts appear to do one thing while actually doing quite another. Just as the eponymous character of Bizango, the "human chameleon, " takes on the appearance of others to achieve his goals, Péan's texts camouflage themselves as genre literature. The novels use intertextual engagement to articulate poignant transhistorical and transcultural commentaries on injustice.